Digitalization of the "Al-Fatih" Thematic Dictionary to Enhance Arabic Language Learning - La Tadzarney Varda; Hanik Mahliatussikah; Imam Asrori (Asalibuna, 2026)
Learning vocabulary is a fundamental task for students to master Arabic. Therefore, it is important for students to learn vocabulary to facilitate their mastery of Arabic. In fact, students' lack of understanding of vocabulary is one of the factors that hinder the learning of Arabic. This study aims to 1) Develop a digital thematic dictionary for Arabic language learning; 2) Describe the feasibility of a digital thematic dictionary for Arabic language learning; 3) Analyze the effectiveness of a digital thematic dictionary for Arabic language learning among MA Darul Faqih students. This study uses the ADDIE development method, which consists of 1) analyzing needs; 2) designing; 3) developing the product; 4) implementing; and 5) evaluating. The researcher used SPSS to calculate the t-test to determine whether there was a significant difference between before and after the implementation of the digital thematic dictionary .The data used in this study were the results of needs analysis obtained through observation and questionnaires, development assessment results, and pre-test and post-test scores. The data sources were students, Arabic language teachers, and subject matter and media experts. Meanwhile, the data collection techniques used were observation, interviews, and questionnaires. The results of this study are: 1) A digital thematic dictionary developed based on the Arabic language textbook for first-year high school students published by the Ministry of Religious Affairs in 2019. 2) The validation test results from subject matter experts were 88% and from media experts were 84%, indicating that the dictionary is suitable for use in Arabic language learning. 3) The results of the t-test analysis on pretest and posttest scores showed a significant increase (t = –6.006; p < 0.001), indicating that the use of the digital thematic dictionary learning media has a positive impact on students' learning outcomes.